2019
DOI: 10.11609/jott.4944.11.10.14249-14258
|View full text |Cite
|
Sign up to set email alerts
|

Species diversity and spatial distribution of amphibian fauna along the altitudinal gradients in Jigme Dorji National Park, western Bhutan

Abstract: This paper presents the results of a study conducted on the diversity and spatial distribution of amphibian fauna in two different habitat types along the elevation gradients of Mochu River valley in Jigme Dorji National Park, Bhutan.  The survey was conducted from November 2017 to February 2019.  The study aimed to assess the diversity and distribution of amphibians using an opportunistic visual encounter survey technique.  A total of 16 species of amphibians belonging to nine genera distributed among seven f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…(viridimaculatus group)" pending a detailed taxonomic study of voucher specimens from the locality. Koirala et al (2019) reported four species of Amolops (A. marmoratus, A. mantzorum, A. monticola and an unidentified Amolops species) from Jigme Dorji National Park (but gave no specific localities) in western Bhutan. A photograph of A. marmoratus (image 4) represents an A. cf.…”
Section: Review Of Amolops Reports From Bhutanmentioning
confidence: 99%
See 1 more Smart Citation
“…(viridimaculatus group)" pending a detailed taxonomic study of voucher specimens from the locality. Koirala et al (2019) reported four species of Amolops (A. marmoratus, A. mantzorum, A. monticola and an unidentified Amolops species) from Jigme Dorji National Park (but gave no specific localities) in western Bhutan. A photograph of A. marmoratus (image 4) represents an A. cf.…”
Section: Review Of Amolops Reports From Bhutanmentioning
confidence: 99%
“…Wangyal et al (2020) did not refer to Koirala et al's (2019) prior identification. The field work in Koirala et al (2019) was reported to have been carried out from November 2017 to February 2019, however, the photo voucher in Wangyal et al (2020) was reported to have been taken on 20 July 2019, indicating a discrepancy in the date that the photo vouchered animal was observed between these two papers. As mentioned above the individual photographed in both studies represents a juvenile viridimaculatus species group member; A. wenshanensis is a member of the morphologically disparate monticola species group (Yuan et al, 2018).…”
Section: Review Of Amolops Reports From Bhutanmentioning
confidence: 99%
“…The existence of these few species is most likely the result of disturbances produced by frequent public visits to RPTN Rawa Bunder. The habitat degradation could be due to the high adaptability of the species to the environment (Koirala et al 2019).…”
Section: Amphibians Habitatmentioning
confidence: 99%
“…In Bhutan, the Rhacophoridae are represented by four species: two from the genus Polypedates and two Rhacophorus species (Wangyal 2014;Das et al 2016;Tshewang & Letro 2018;Koirala et al 2019). Rhacophorus smaragdinus (Blyth, 1852) formerly Rhacophorus maximus, was reported from Zhemgang (Wangyal 2014) and Jigme Dorji National Park (Koirala et al 2016).…”
Section: Open Accessmentioning
confidence: 99%
“…In 2016, Rhacophorus bipunctatus Ahl, 1927 was reported from Royal Manas National Park (Das et al 2016). Currently, the anuran fauna of Bhutan is represented by 83 recognized species distributed among seven genera (Das et al 2016;Nidup et al 2016;Tshewang & Letro 2018;Koirala et al 2019;Wangyal 2013Wangyal , 2014Tenzin & Wangyal 2019;Wangyal & Gurung 2017;Wangyal et at. 2020).…”
Section: Open Accessmentioning
confidence: 99%